Pension reform and social development of Ukraine: problems and development prospects - Rad, Natalia (Skhid, 2013)
Several aspects of pension system reforming in Ukraine and its impact on qualitative changes in social environment have been analyzed. A wide range of problems has been identified and propositions to improve concepts of pension reforming have been made